Landscape of Molecular Events in Pituitary Apoplexy - Gupta, Prakamya; Dutta, Pinaki (Frontiers in Endocrinology, 2018)
Apoplectic pituitary adenomas cause significant morbidity and even mortality. The pituitary apoplexy denotes a pituitary adenoma presenting with hemorrhage and/or infarction, implementation in remedial effects of various of drugs in pituitary apoplexy is a promising pharmacogenomic field in the near future adenoma treatment. Indisputably, this is an important horizon for complicated pituitary adenomas. In a pituitary adenoma, the interplay between genetic, cytokine, and growth factors promotes the pathogenic transformation into an apoplectic formation. However, till date, little is known about how all these factors together lead to the pathogenesis of apoplectic pituitary. The vascular endothelial growth factor, tumor necrosis factor-α (TNF-α), pituitary tumor-transforming gene (PTTG), matrix metalloproteinase-2/9 (MMP-2/9), proliferating marker (Ki-67), as well as hypoxia-inducing factor are the major contributing factors involved in pituitary apoplexy. The molecular mechanism involved in pituitary apoplexy has never been described so far. In this review, we discuss the various proteins/cytokines/growth factors and signaling molecules which are involved in the pathogenesis of pituitary apoplexy and their potential role as biomarkers or as therapeutic targets.